2016
DOI: 10.1016/j.jvs.2016.03.410
|View full text |Cite
|
Sign up to set email alerts
|

Branched versus fenestrated endografts for endovascular repair of aortic arch lesions

Abstract: Both fTEVAR and bTEVAR are feasible for the treatment of aortic arch diseases in high-risk patients. Results are promising, although fTEVAR was associated with higher mortality in this early experience. bTEVAR was more commonly used in Ishimaru zone 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
108
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 20 publications
0
108
0
6
Order By: Relevance
“…Compared with extra-anatomical bypass and branched endografting, the incidence of neurological sequelae with the chimney technique is lower due to less manipulation of target vessels and the aortic arch. 6,9,10,28 In the current study, 32 (28.1%) of 114 LCCA chimneys were deployed via a percutaneous approach, and all the chimneys in the IA were inserted via a right brachial access. The only stroke was caused by migration and compression of the chimney grafts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with extra-anatomical bypass and branched endografting, the incidence of neurological sequelae with the chimney technique is lower due to less manipulation of target vessels and the aortic arch. 6,9,10,28 In the current study, 32 (28.1%) of 114 LCCA chimneys were deployed via a percutaneous approach, and all the chimneys in the IA were inserted via a right brachial access. The only stroke was caused by migration and compression of the chimney grafts.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported favorable results using fenestrated/branched techniques in aortic arch pathologies. [3][4][5][6][7] However, this approach is limited by the morphological diversity of the aortic arch, necessitating patient-specific and tailor-made devices. Moreover, the procedures are complex and time-consuming, often inapplicable in emergency situations, and place a considerable financial burden on the patient, limiting their clinical usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore difficult to judge how easily these outcomes can be translated to other centres. Other series presented in the literature 5,6,10,20 also reflect the experience of highly experienced centres.…”
Section: Discussionmentioning
confidence: 92%
“…The data presented are comparable with those from Tsilimparis and colleagues 6 in Hamburg, who performed branched thoracic endovascular aortic repair in 14 patients with an operative mortality rate of 0 per cent, stroke 7 per cent (1 patient) and no cases of spinal cord ischaemia or renal failure. These results were favourable when compared with the use of fenestrated devices in the aortic arch in 15 patients, which was associated with an operative mortality rate of 20 per cent (3 patients) and stroke rate of 14 per cent (2 patients) 6 .…”
Section: Discussionmentioning
confidence: 97%
“…Finally these fenestrated stent-graft are ‘off the shelf’ so they can be used for emergency procedures. They avoid the potential risks of guttering with Chimney stent-grafts and the financial costs of T branch devices, which require much more stock [15]. …”
Section: Discussionmentioning
confidence: 99%